A Case of Using Hominis Placenta and Soyeom Mixed Pharmacopuncture to Remove Melanocytic Nevus - Hyung-Sik Seo (Korean Pharmacopuncture Institute, 2018)
Objective:It has been attempted to find out that Homine Placents and Soyeom mixed Pharmacopuncture (HSP) procedure is effective for the removal of melanocytic nevus of considerable size which cannot be applied to general acupuncture.Methods:Hominis placenta (0.5ml) and Soyeom (0.5ml) mixed pharmacopuncture (1.0ml) was subcutaneously injected in several places of melanocytic nevus. The treatment was performed about 20 times, once a week. Layer analysis of pigmentation was carried out using ECOSKIN.Results:One year after the HSP procedure, the pigmentation of the melanocytic nevus was slightly reduced and completely removed after 2 years of procedure.Conclusion:The HSP could be effective for removing hyperpigmentation in the melanocytic nevus.